The Libertarian Government and its Foreign and Security Policy - Jeziorny, Dariusz (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
Among the aims of this text is: firstly, to characterize how the libertarians think about security of the citizens’ life and property in the case of aggression, or the possibility of aggression, from abroad. Secondly, to explore how they imagine the world-wide international order and a libertarian government’s participation in it and finally to attempt an assessment of how effective the libertarian concepts proposed by the variously quoted authors could operate or be harnessed or implemented or even embraced in a governmental context. It should be possible through this article to compare and cross check whether or not the ideas focusing on foreign and security policy unite particular libertarians.